RICE ROOT SYSTEM SPATIAL DISTRIBUTION CHARACTERISTICS AT FLOWERING STAGE AND GRAIN YIELD UNDER PLASTIC MULCHING DRIP IRRIGATION (PMDI) - H. B. He; R. Yang; L. Chen; H. Fan; X. Wang; S. Y. Wang; H. W. Cheng; F. Y. Ma (Journal of Animal and Plant Sciences, 2014)
Plot experiments and field investigations were conducted with NingGeng28 (japonica) in 2011 and 2012 to investigate rice root spatial distribution at flowering and grain yield under PMDI. The results showed that fewer roots at the 0–20 cm soil layer were present under PMDI than under flooding irrigation, but more roots were observed at 20–60 cm soil layer under PMDI than under flooding irrigation. In the horizontal direction, the root length density (RLD) at the 0–20 cm soil layer decreased with increasing horizontal distance away from the hill sites (A1 > B1 > C1) and signiﬁcantly decreased with decreasing irrigation application amount in each soil column. At the 20–40 cm and 40–60 cm soil layers, RLD were relatively constant under flooding irrigation but increased with increasing horizontal distance away from the hills under PMDI (C2 > B2 > A2；C3 > B3 > A3) and signiﬁcantly increased with decreasing irrigation application amount in each soil column. Significant differences in roots and aboveground performance were observed between the near and far rows. Moreover, the grain yield ranged from 3.35×103 Kg ha-1 to 6.86×103 Kg ha-1 under PMDI, which was 19.3–60.31% lower than that under flooding irrigation. Correlation analysis showed that the roots at the A1 and B1 sites were positively significantly correlated with yield components and aboveground agronomic traits. Therefore, improving root development at the A1 and B1 sites at flowering stage could be a key factor to obtain higher grain yield and good agronomic performance under PMDI.`
Keywords: Rice; Plastic mulching drip irrigation; Root distribution characteristics; Grain yield